Coarse-grained nucleic acid–protein model for hybrid nanotechnology. Issue 13 (5th January 2021) - Procyk, Jonah; Poppleton, Erik; Šulc, Petr
Abstract : A coarse-grained model for analysis and design of hybrid DNA-protein nanoscale structures. Abstract : The emerging field of hybrid DNA–protein nanotechnology brings with it the potential for many novel materials which combine the addressability of DNA nanotechnology with the versatility of protein interactions. However, the design and computational study of these hybrid structures is difficult due to the system sizes involved. To aid in the design and in silico analysis process, we introduce here a coarse-grained DNA/RNA–protein model that extends the oxDNA/oxRNA models of DNA/RNA with a coarse-grained model of proteins based on an anisotropic network model representation. Fully equipped with analysis scripts and visualization, our model aims to facilitate hybrid nanomaterial design towards eventual experimental realization, as well as enabling study of biological complexes. We further demonstrate its usage by simulating DNA–protein nanocage, DNA wrapped around histones, and a nascent RNA in polymerase.